2015
DOI: 10.1111/1475-4932.12226
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Education in Productivity Growth in Australia, 1860–1939

Abstract: Despite a significant literature comparing Europe and the USA, and linking education and human capital to growth and development, there is virtually no research in the Australian context which attempts to investigate this link empirically. Australia is an interesting case because it was one of the world's wealthiest nations in the late nineteenth century. The economy was built on agriculture and mining, but there was no obvious evidence of a natural resource curse despite losing ground on the leading nations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Therefore, educational funding promotes economic growth, human development, and a reduction in unemployment. Specifically, education funding will assist the country in achieving appropriate or sustainable economic growth [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ]. That is because every human being is a resource for society, and spends on training human beings to gain various skills and knowledge, which positively influences national development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, educational funding promotes economic growth, human development, and a reduction in unemployment. Specifically, education funding will assist the country in achieving appropriate or sustainable economic growth [ [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ]. That is because every human being is a resource for society, and spends on training human beings to gain various skills and knowledge, which positively influences national development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The link between education and productivity has been examined in a number of studies (Bradley et al , 2010; Banerjee and Wilson, 2016; Edvardsen et al , 2017; Li et al , 2018; Drakh et al , 2021; Balwant et al , 2022), the results of which show there is an influential relationship. In terms of the financial aspect, several studies have investigated the impacts of financial inclusion (Ghosh and Sahu, 2021; Peprah et al , 2021; Ghosh and Sahu, 2022), financial literacy (Lopus et al , 2019) and financial planning (Tilai et al , 2022) on productivity, which were also found to be significant.…”
Section: Introductionmentioning
confidence: 99%